Injectable Hydrogel through Hydrophobic Grafting on Chitosan for Controlled Drug Delivery - Mahanta A.K.; Maiti P. (My University, 2025)
An injectable hydrogel of chemically modified chitosan has been developed for controlled drug delivery application. Highly hydrophilic chitosan is chemically modified through grafting of ester-diol based polyurethane to transform into hydrogel through hydrophilic-hydrophobic balance. Grafting is confirmed through different spectroscopic techniques such as 13C NMR, UV-visible, and FTIR. Grafted copolymer shows higher contact angle as well as poorer swelling than pure one. Hydrogel of graft copolymer is made in dilute acetic acid medium. Surface morphology of the hydrogel, as investigated through SEM, exhibits an interconnected porous network suitable for drug delivery vehicle. In vitro drug release kinetics reveals that the graft copolymer releases the drug in a sustained manner as compared to the pure one. Two types of model drugs (antibacterial tetracycline hydrochloride and anticancerous doxorubicin hydrochloride) are used for release study to check the control release for various applications. The cytotoxicity of the newly developed hydrogel is accessed using the B16-F10 melanoma cell line, and the hydrogel is found to have a better biocompatible nature than that of pure chitosan. Cellular uptake of drug from graft copolymer hydrogel has considerably increased vis-à-vis pure drug resulting in significant enhancement of cell killing using the developed drug embedded hydrogel system. In vivo gelation study in an animal model verifies that the graft copolymer has the fine ability to be used as an injectable hydrogel for disease control. Hence, the developed graft copolymer has the potential to be used as an injectable hydrogel as a controlled drug delivery vehicle. © 2019 American Chemical Society.